POLARIZATION OF LOCAL COMMUNITY PERCEPTION ON SOCIOCULTURAL DYNAMICS IN ECOTOURISM DEVELOPMENT OF BOPUNJUR, WEST JAVA - Gatot Widodo; Ricky Avenzora; Elly Malihah; Tutut Sunarminto (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2023)
In addition to providing multiplier economic benefits, the tourism sector also has the potential to cause some latent and massive negative social impacts. For this reason, it is important to map out the orientation of the local community. This study analyzes the polarization of the local community's perceptions of sociocultural dynamics in the ecotourism development area. The local community that became the focus of the research consisted of five groups of respondents: traditional leaders, religious leaders, educational leaders, community leaders, and tourism actors. This research was conducted in the Bopunjur Ecotourism Area, Bogor Regency, West Java, precisely in seven ecotourism destinations, namely Ciawi, Caringin, Cibogo, Cipayung, Megamendung, Cisarua, and Tugu. This study used mixed methods, qualitative and quantitative approach. Data collection on social and cultural dynamics was done by distributing questionnaires to the respondents. The research instrument was a questionnaire designed closed-ended with guidance on one score-one indicator scoring system. The results showed that positive social situations, namely conducive situations, associations, cooperative situations, and productive collaborations were still more dominant than negative social situations: war, conflict, and dissociation. The polarization of the local community on sociocultural dynamics has a positive direction with a polarization scale that is aligned with each other so that there is an excellent opportunity to build productive collaboration among stakeholders in this area